2006
DOI: 10.1111/j.1365-2710.2006.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve adherence to medication in people with type 2 diabetes mellitus: a review of the literature on the role of pharmacists

Abstract: Summary Background and objective:  Pharmacists are now adopting a crucial role in the management of chronic illness in primary care, providing diabetes care and advice. This review aims to show whether a range of diabetes care interventions delivered by pharmacists is successful in improving adherence to medication. Methods:  The studies reviewed formed a subgroup of a Cochrane review on interventions to improve adherence to medication in people with type 2 diabetes. Search terms were ‘type 2 diabetes mellitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
2
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 36 publications
6
110
2
6
Order By: Relevance
“…Tsuyuki et al (2002) demonstrated that pharmaceutical interventions improved the process of controlling cholesterol in high-risk patients, and Castro et al (2006) demonstrated a tendency toward better blood pressure control in resistant hypertensive patients who participated in a PC program (Castro et al, 2006). Lindenmeyer et al (2006) noted whether the intervention made by pharmacists (in approximately 21 studies) in the care of diabetics had improved adherence to medication treatment, which indicated potential benefits specifically from better educating patients (Lindenmeyer et al, 2006). These results support our findings that 82% of NOMs related to necessity were at least resolved, which implies the improvement and/or adequacy of the reference values of the majority of patients in their anthropometric parameters and lipid profiles.…”
Section: Discussionsupporting
confidence: 81%
“…Tsuyuki et al (2002) demonstrated that pharmaceutical interventions improved the process of controlling cholesterol in high-risk patients, and Castro et al (2006) demonstrated a tendency toward better blood pressure control in resistant hypertensive patients who participated in a PC program (Castro et al, 2006). Lindenmeyer et al (2006) noted whether the intervention made by pharmacists (in approximately 21 studies) in the care of diabetics had improved adherence to medication treatment, which indicated potential benefits specifically from better educating patients (Lindenmeyer et al, 2006). These results support our findings that 82% of NOMs related to necessity were at least resolved, which implies the improvement and/or adequacy of the reference values of the majority of patients in their anthropometric parameters and lipid profiles.…”
Section: Discussionsupporting
confidence: 81%
“…A pharmacist-patient relationship of mutual trust and understanding is established through dialogue. 13,30 The lack of experience in the pharmacy at this point could have attributed to the lack of confidence in communicating with patients, as indicated later in the slight increase from pre to post-training responses to Question 11. A comparison of the changes in student self-efficacy belief responses from the Hagemeier and colleague's study and the Japanese student responses in this study reflected similar progress in more effective interpersonal communication from pre to post training.…”
Section: R a F Tmentioning
confidence: 99%
“…[11][12][13][14] Medication therapy management (MTM), one of the well-established roles of pharmacists, could be used as one of the effective approaches to improve adherence to anti-diabeic medications and health outcomes. 7,15 Furthermore, clinical pharmacists, with their pharmacotherapeutic knowledge and patient centered training, are uniquely positioned to educate, elaborate, implement and monitor patients on medication therapies, which ultimately results in better health outcomes. 7,[16][17][18] Cognizant of the global paradigm shift in pharmaceutical education and practice, Public universities in Ethiopian revised their undergraduate pharmacy curriculum in 2008 to be more patient focused and a limited number of pharmacy schools also started a postgraduate course in clinical pharmacy.…”
Section: Original Researchmentioning
confidence: 99%
“…7,15 Furthermore, clinical pharmacists, with their pharmacotherapeutic knowledge and patient centered training, are uniquely positioned to educate, elaborate, implement and monitor patients on medication therapies, which ultimately results in better health outcomes. 7,[16][17][18] Cognizant of the global paradigm shift in pharmaceutical education and practice, Public universities in Ethiopian revised their undergraduate pharmacy curriculum in 2008 to be more patient focused and a limited number of pharmacy schools also started a postgraduate course in clinical pharmacy. Even though there has been an increase in pharmacists' involvement in patient care in Ethiopia, their full potential and role in clinical practice is yet to be explored.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation